Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. The reality of applying the principles of university governance at the University of Idlib from the Perspective of Faculty Members Mr. Ahmad Mohamad Staif, Co-Prof. Siham Mustafa Abdulaziz, Dr. Hisham Farag Abd Alsid 2. The reality of reflective practices in action research and its difficulties from the point of view of a random sample of primary school teachers at Umm Al-Muminin Aisha School in Al-Zulfi Governorate Mrs. Lulwah Abdullah Al-Fahd, Co-Prof. Abeer Mohammed Al-Arfaj 3. Using the museum education in teaching kindergarten children from the point of view of kindergarten teachers in Medina city Mrs. Esraa Emad Kurdi, Co-Prof. Kawther Jamil Belgoun 4. The effect of using artificial intelligence applications in improving selective attention of students with learning disabilities in the primary stage Mrs. Enas Attia Alghamdi , Mrs. Sahar Hamdan Alghamdi , Dr. Leena Ahmad Alfarani 5. Teaching attitudes among Arabic language teachers of Arabic for non-native speakers in The Sultanate of Oman Mr. Amer Salim Hamad Al-Isaee , Dr. Saif Nasser Saif Al-Azri 6. Obstacles to scientific publishing in scientific journals classified within the (ISI) and (Scopus) databases from the point of view of faculty members in some universities in Arab countries Prof. Maha Abdullah Al-Dabbagh